2019
DOI: 10.1111/neup.12556
|View full text |Cite
|
Sign up to set email alerts
|

Primary cervical spine AL‐κ amyloidoma: A case report and review of the literature

Abstract: Of the myriad of variants of amyloidoses where abnormally folded proteins damage native tissue, primary cervical spine amyloidoma represents one of the rarest forms. Since clinical presentations and imaging findings appear similar to other pathologies, including abscesses, metastatic lesions, and inflammatory lesions, a definitive diagnosis requires a biopsy with specific immunohistochemical stains. We present the first known case of primary cervical amyloid light‐chain (AL)‐κ subtype amyloidoma and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Common physical exam findings include objective weakness, paralysis, and hyperreflexia [21]. MRI imaging often reveals hypointense structures on T1 and T2 images and mostly occupies the epidural space and bone at the C1, C2, C6 and C7 levels [2,21]. These findings were concurrent with our case and with what has been previously reported in ATTR-specific cases.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Common physical exam findings include objective weakness, paralysis, and hyperreflexia [21]. MRI imaging often reveals hypointense structures on T1 and T2 images and mostly occupies the epidural space and bone at the C1, C2, C6 and C7 levels [2,21]. These findings were concurrent with our case and with what has been previously reported in ATTR-specific cases.…”
Section: Discussionsupporting
confidence: 88%
“…Presently, there are 40 known human amyloid fibril proteins, most of which are exceedingly rare [3]. Of the known proteins, commonly reported amyloidoma types include immunoglobin light chain (AL), serum amyloid A (AA), and β2-microglobulin (Aβ2M); less commonly is the transthyretin type [21,28]. Most often, reported cases are attributed to either AL or Aβ2M types [2,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1863 Rudolf Virchow observed abnormal deposits of a substance he called "amyloid." This disease has systemic (the most frequent) and localized forms (unusual intracellular or extracellular deposits) [5]. Among the clinical manifestations of amyloidosis, the most frequent is renal, with patients with renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, destructive spondyloarthropathy has been reported in patients with amyloidosis secondary to renal dialysis, which causes amyloid deposits in the joints, intervertebral discs, ligaments and vertebral bodies ales with the consequent myelopathy or radiculopathy [7]. In 2015 Liu et al [8] reported a case with circumferential intrathecal ossification secondary to oculoleptomeningeal amyloidosis and as recently as 2019 2019 Rotter et al [5]. reported the first case of focal intradural primary amyloidoma of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%